Enhancing Public Trust in Islamic Boarding Schools through Electronic Word of Mouth (E-WOM): A Symbolic Interactionism Analysis - Baharun, Hasan; Hasanah, Sofiyatul (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2023)
This study explores the impact of Electronic Word of Mouth (E-WOM) on public trust in Islamic boarding schools, using Nurul Jadid Islamic Boarding School as a case study. Applying symbolic interactionism, the research aims to understand how E-WOM shapes public perceptions in this educational context. A qualitative approach employing naturalistic phenomenology and descriptive analysis involving observations, interviews, and documentation was used. The findings indicate that E-WOM, utilized since 2018 at Nurul Jadid, has significantly enhanced the school's public image and trust, notably increasing student enrollment and international attention. Key strategies include effective digital content creation and audience engagement. However, the study’s focus on a single institution suggests the need for broader research to generalize these findings. Implications for educational administrators and policymakers include strategic insights for digital communication and public engagement. This research contributes to the academic discourse in communication and educational studies, offering a novel application of symbolic interactionism in digital communication. Future research should examine E-WOM’s long-term effects on institutional reputation and explore its application in diverse educational settings.